The Pressure of Carbon Loss in Industrial Upgrading: Pathways and Challenges of Low-Carbon Transition in China’s Manufacturing Sector - Zhihao Liu; Qirui Zhou (Law and Economy, 2024)
China’s manufacturing sector, the largest globally, is at the forefront of the country’s efforts to transition to a low-carbon economy amidst growing domestic and international pressures. As China commits to peaking carbon emissions by 2030 and achieving carbon neutrality by 2060, the sector faces significant challenges in balancing economic growth with substantial carbon reductions. This paper explores the pathways and challenges of achieving a sustainable low-carbon transition in China’s manufacturing sector. It examines the pressures of carbon loss on industrial upgrading, the potential of technological innovation and digital transformation, the role of green finance, and the importance of policy and regulatory measures. The analysis highlights the key barriers, such as economic costs, technological constraints, regulatory inconsistencies, and social impacts, while providing strategic recommendations to foster a balanced transition. By integrating policy support, technological advancement, financial incentives, and international cooperation, China can navigate its journey toward a low-carbon manufacturing sector, ensuring long-term economic sustainability and environmental goals.